The Enactment of Multilingualism in Secondary School: The Study of English Education Students’ Perceptions - Damayanti, Alvira; Muliati M., Andi; Muhalim, Muhalim (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
The purpose of this study is to determine English Education Students as the pre-service teacher perceptions on the enactment of multilingualism in secondary school, from the general views on multilingualism practice, until the benefit and threat to multilingualism practice by the use of dominant language in the learning process. The study used interview to collect data from four participants who are experienced in teaching multilingual students in national schools. The data were analysed using thematic method which shows seven themes from three main indicators of the study. The findings show that in general, the participants perceive that there is strong relation between the learning of Indonesian and English. Multilingualism is one of important key for medium of knowledge transfer, and they also state their opinion about needs of regulation for learning. Further, they perceive that the benefit of multilingualism covers the contextual understanding for teaching English subject in the class and facilitates flexible interaction between teacher and students. However, the participants also state their view on the threat of the existence of multilingualism in schools that can be caused by the dominant use of English in class which can affect the decline in the use of local languages and Indonesian. To overcome the problem, they suggest mitigations that can be done to overcome this problem by encouraging clear rules for the use of language integration in class and maximize the role of extracurricular activities to maintain the existence of multilingualism.   Keywords: multilingualism, secondary school, perceptions